Reformar el art. 155 del código orgánico de organización territorial, autonomía y descentralización, en cuanto a insertar nuevas sanciones por incumplimiento de disposiciones y obligaciones de las autoridades o funcionarios públicos - Carreño Loaiza, Cilvia Alisandra (2016)
Accordance with the constitutional rules and specifically in article 229, of the Constitution of the Republic of Ecuador, we have that persons who in any way or under any title, work or provide services, or exercising a position, function or dignity within the public sector have the quality of servants and public servants. However, it is known to all that a good servers municipal sector is characterized by inefficiency, inefficiency and negligence in the performance of their functions, at the same time causing discontent and hostility, to cause an inevitable distrust of citizenship This situation is due to the large number of improvised staff located by political commitments, which lack suitable profiles in the discharge of public office; and, the lack of establishing sanctions to servers that do not meet their duties fully, by the respective authorities The organic code of Territorial Organization, autonomy and decentralization, in article 155, says: "the authorities or public officials who fail to comply with the provisions and indicated obligations, within certain deadlines in the Constitution, this code and by the National Council's competencies, shall be punished by the removal of duties by the appointing authority, at the request of the National Council's competenciesfollowing the corresponding administrative procedure and respecting the guarantees of due process. This sanction will be communicated to the General Comptroller of the State for the respective legal purposes. Failure to comply with the obligations referred to in this code, shall be reason prosecution political by the legislative function, if it were authorities controlled by this role of the State"just say that sanctions are established for the authorities or public officials who fail to comply with the provisions and obligations indicated, in the Constitution in the code and by the National Council, but these sanctions are administrative, and not been able to comply the role for which were created, so the coercive sanction is a measure which not only official jeopardizes their work but also a lot more precious asset as it is freedom, as well as more than criminal liability also the civilas it has broken individual rights, in the exercise of their functions To do this, it is necessary, establish new disciplinary measures, in such a way that may require a full implementation of the functions of municipal servers, since with the current has not achieved efficiency in service; because of that, the lack of quality, effectiveness and efficiency in the performance of a large number of officials of municipal bodies, they have currently generated an imbalance in obligations that councils should be for the benefit of its constituents.